BUSINESS ADAPTATION STRATEGIES POST-COVID-19 PANDEMIC : A STUDY OF THE TOURISM SECTOR IN ACEH - Kiki Putri Amelia (GLOBAL RESEARCH IN ECONOMICS AND ADVANCE THEORY (GREAT), 2024)
The COVID-19 pandemic severely disrupted the global tourism sector, and Aceh—once on a positive growth trajectory—was no exception, with tourist arrivals plummeting by over 70% in 2020, resulting in revenue losses, layoffs, and business closures. This study examines the adaptation strategies employed by Aceh’s tourism stakeholders in the post-pandemic period using a qualitative descriptive approach through in-depth interviews, observations, and document analysis involving 15 business owners from hotels, restaurants, travel agencies, and tour operators, with thematic analysis applied to identify patterns and effective practices. The findings reveal four key strategies: digital transformation via online marketing, booking platforms, and virtual tours; service diversification through health and wellness tourism packages; stakeholder collaboration to promote Aceh as a safe destination and enforce health protocols; and sustainable tourism initiatives, including eco-friendly practices and community engagement. These measures enhanced customer engagement, strengthened destination branding, and facilitated gradual recovery, although challenges such as limited capital, changing traveler behavior, and stringent regulations persist, particularly for small operators. The study contributes to the literature on business adaptation in tourism and offers practical recommendations for industry actors, policymakers, and local communities, emphasizing innovation, collaboration, and sustainability as essential pillars of resilience while underscoring the need for continued support to ensure long-term viability in the post-pandemic era.